The discovery and enhanced properties of trichain lipids in lipopolyplex gene delivery systems. Issue 4 (10th January 2019) - Mohammadi, Atefeh; Kudsiova, Laila; Mustapa, M. Firouz Mohd; Campbell, Frederick; Vlaho, Danielle; Welser, Katharina; Story, Harriet; Tagalakis, Aristides D.; Hart, Stephen L.; Barlow, David J.; Tabor, Alethea B.; Lawrence, M. Jayne; et al.
Abstract : Novel trichain lipids have been identified with enhanced transfection properties in lipopolyplexes. Abstract : The formation of a novel trichain (TC) lipid was discovered when a cationic lipid possessing a terminal hydroxyl group and the helper lipid dioleoyll -α-phosphatidylethanolamine (DOPE) were formulated as vesicles and stored. Importantly, the transfection efficacies of lipopolyplexes comprised of the TC lipid, a targeting peptide and DNA (LPDs) were found to be higher than when the corresponding dichain (DC) lipid was used. To explore this interesting discovery and determine if this concept can be more generally applied to improve gene delivery efficiencies, the design and synthesis of a series of novel TC cationic lipids and the corresponding DC lipids was undertaken. Transfection efficacies of the LPDs were found to be higher when using the TC lipids compared to the DC analogues, so experiments were carried out to investigate the reasons for this enhancement. Sizing experiments and transmission electron microscopy indicated that there were no major differences in the size and shape of the LPDs prepared using the TC and DC lipids, while circular dichroism spectroscopy showed that the presence of the third acyl chain did not influence the conformation of the DNA within the LPD. In contrast, small angle neutron scattering studies showed a considerable re-arrangement of lipid conformation upon formulation as LPDs, particularly of the TC lipids, while gel electrophoresis studies revealed that the use of a TC lipid in the LPD formulation resulted in enhanced DNA protection properties. Thus, the major enhancement in transfection performance of these novel TC lipids can be attributed to their ability to protect and subsequently release DNA. Importantly, the TC lipids described here highlight a valuable structural template for the generation of gene delivery vectors, based on the use of lipids with three hydrophobic chains.